2021
DOI: 10.1038/s41467-021-23806-5
|View full text |Cite
|
Sign up to set email alerts
|

RPA shields inherited DNA lesions for post-mitotic DNA synthesis

Abstract: The paradigm that checkpoints halt cell cycle progression for genome repair has been challenged by the recent discovery of heritable DNA lesions escaping checkpoint control. How such inherited lesions affect genome function and integrity is not well understood. Here, we identify a new class of heritable DNA lesions, which is marked by replication protein A (RPA), a protein primarily known for shielding single-stranded DNA in S/G2. We demonstrate that post-mitotic RPA foci occur at low frequency during unpertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…S6B,C " type="url"/> ) demonstrating normal DNA damage repair kinetics in mutant spermatocytes and suggesting the aberrant γH2AX signal is not a result of persistent or recurring DNA damage. Previous work has suggested that some DNA double strand breaks may not be marked by RPA ( Lezaja et al, 2021 ); thus, as a secondary assessment, we examined relative levels of the 9-1-1 DNA damage recognition complex as indicated by RAD9 ( Parrilla-Castellar et al, 2004 ) and activation of NHEJ marked by Ku80 ( Fell and Schild-Poulter, 2015 ; Ma et al, 2018 ) ( ).…”
Section: Resultsmentioning
confidence: 99%
“…S6B,C " type="url"/> ) demonstrating normal DNA damage repair kinetics in mutant spermatocytes and suggesting the aberrant γH2AX signal is not a result of persistent or recurring DNA damage. Previous work has suggested that some DNA double strand breaks may not be marked by RPA ( Lezaja et al, 2021 ); thus, as a secondary assessment, we examined relative levels of the 9-1-1 DNA damage recognition complex as indicated by RAD9 ( Parrilla-Castellar et al, 2004 ) and activation of NHEJ marked by Ku80 ( Fell and Schild-Poulter, 2015 ; Ma et al, 2018 ) ( ).…”
Section: Resultsmentioning
confidence: 99%
“…The converse may be true for POLQ – / – clones undergoing a telomere-driven crisis, so that cell cycle progression and population doubling rates may be expedited, with reduced opportunity for corrective DNAR that safeguards genomic integrity. As POLQ plays an important role in the rescue of intermediates of aborted HR that materialize late in the cell cycle ( 22 ), frustration of TMEJ may also deter cell cycle pausing pre-mitosis, so that chromosomal damage persists ( 98 , 99 ), is extruded into micronuclei (MN) ( 100 ) or triggers apoptosis without suspension of proliferation. In concert with the skewed distributions of inter- and intra-chromosomal telomere fusions (Figure 3A ), POLQ deficiency supports long-range DNA recombinations that precipitate genomic heterogeneity ( 100 ), manifest in the polyclonal post-crisis populations ( Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These RPA foci colocalize with single stranded DNA that escaped the previous cell cycle, and they predominantly associate with telomeric regions. Knocking down RAD52 reduced G1-associated RPA foci indicating that these regions might have been primed by RAD52 in the previous mitosis [ 154 ].…”
Section: Mechanisms For Managing Replication Stressmentioning
confidence: 99%